Challenges of International Collaborative Governance in Africa - Mbandlwa, Zamokuhle (Journal of Cultural Analysis and Social Change, 2025)
International collaborative governance has become increasingly essential in addressing complex global challenges, such as climate change, global health crises, and transnational security threats. This research aims to explore the multifaceted challenges faced by international actors in their efforts to govern collaboratively on a global scale. The primary objectives of this research are to identify the key challenges impeding effective international collaborative governance, assess their impact on global decision-making, and propose recommendations for overcoming these challenges. We aim to contribute to a deeper understanding of the obstacles facing international cooperation and the strategies that can enhance its effectiveness. To achieve these objectives, this study employs a mixed-methods approach. Quantitative data collection involves surveys and analysis of international agreements, treaties, and declarations, while qualitative data is gathered through expert interviews and content analysis. The research sample encompasses diverse international organizations, state actors, and civil society groups. The study reveals a range of challenges, including sovereignty concerns, power imbalances, and the difficulties of enforcing international agreements. Quantitative data demonstrate that a significant number of international agreements face non-compliance issues, and power disparities hinder equitable decision-making processes. Qualitative data provide insights into the practical complexities faced by international actors. International collaborative governance is crucial for addressing global issues, but it faces formidable challenges. The findings suggest the need for innovative mechanisms to overcome sovereignty concerns, promote equitable participation, and enhance the enforcement of agreements. Future research should focus on exploring potential solutions and their feasibility to strengthen global collaborative governance and ensure a more effective response to pressing global challenges.